2022
DOI: 10.29328/journal.jpsp.1001087
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of senegalese races of Xanthomonas oryzae PV. oryzae to identify resistance genes to use

Abstract: Bacterial blight (BB), is a disease caused by Xanthomonas oryzae PV. oryzae (Xoo), was first reported in Senegal by Trinh in 1980. BB represents a severe threat to rice cultivation in West Africa. Characterizing the pathotypic diversity of bacterial populations is a key to the management of pathogen-resistant varieties. Pathogenicity tests show that all strains are virulent on the susceptible rice variety Azucena, and interact differentially with twelve near-isogenic rice lines, each carrying a single resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…SAHEL 202 (ITA 306) was developed through a hybridization process including TOX 494-3696 and TOX 711/BG 6812. Previous studies conducted byTall et al (2022) demonstrated the resistance of SAHEL 202 to Xoo in Senegal. The results of our study provide additional evidence supporting the resistance of SAHEL 202.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…SAHEL 202 (ITA 306) was developed through a hybridization process including TOX 494-3696 and TOX 711/BG 6812. Previous studies conducted byTall et al (2022) demonstrated the resistance of SAHEL 202 to Xoo in Senegal. The results of our study provide additional evidence supporting the resistance of SAHEL 202.…”
mentioning
confidence: 87%
“…In Senegal, few studies have been conducted with regards to this, and the identi cation of new sources of resistance to bacterial blight. Prior research successfully identi ed cultivars that are partially or highly resistant to Xoo in irrigated rice ecosystems (Tall et al, 2022). However, the disease has recently emerged as a signi cant threat in rainfed ecologies (Islam et al, 2016;Kumar et al, 2020), and currently there is lack of varieties that combine high resistance and good agronomic performance in rainfed conditions.…”
Section: Introductionmentioning
confidence: 99%